54 Relationships Between Heat Stress and Behavioral Responses with Reproductive Traits of Maternal-line Gilts. (7th May 2021) - Cleaver, Kristen N; Hill, Brooklyn A; Johnson, Jay S; Brito, Luiz F
Abstract: Heat stress (HS) during summer months can negatively affect reproductive efficiency and sow productivity. This study was designed to evaluate potential relationships between HS sensitivity and behavior with litter characteristics in replacement gilts. A total of 61 replacement gilts (108.8± 10.4 kg BW; 8 repetitions; 9d/repetition), were tested from February to May 2020 at the USDA-ARS Food Animal Behavior Laboratory in West Lafayette, IN. Pigs were housed (2/pen) in thermoneutral (TN; 22.6± 1.6⁰C) conditions and their behavior was recorded for 5 d. On d 6, gilts were subjected to an open field test and novel object test. Heart rate, number of escape attempts, and vocalizations were recorded during behavior testing. Vaginal temperature monitors were inserted to record body temperature (TB ) every 15 min. Gilts were individually housed and exposed to cyclic HS (28.2± 0.97⁰C nighttime to 36.9± 1.9⁰C daytime; 46± 15.4% relative humidity) on d 7 to 9. Feed was provided ad libitum and feed intake was recorded daily. During the HS challenge, respiration rate (RR), skin (ear, shoulder, rump, and tail) temperature, and posture were recorded every 2 h from 0800 to 2000 h. Following the HS challenge, gilts were transported to the Purdue University swine farm, and gilts that displayed signs of estrus were artificially inseminated (253±29 d of age) between May and September 2020. At farrowing, litter characteristics were obtained and included total number of piglets born, total number of piglets born alive, average litter birth weight, total number of piglets weaned, and average weaning weight of the litter. Correlations between behavior, HS response, and litter characteristics were obtained using JMP 15 software. The preliminary analysis indicated no significant interactions (P < 0.05) between RR or TB with litter characteristics. However additional records are currently being collected, which might reveal important trends among the traits analyzed.